Studi pemanfaatan ekstrak kulit batang jamblang (Syzygium cumini L.) sebagai alternatif pewarna rambut berbasis herbal - Muzakkir , Muzakkir; Sembiring, Fanny Rizki; Indriana , Meutia; Salman, Salman (Journal of Pharmaceutical and Sciences, 2025)
Hair dye is a cosmetic product used to restore or alter hair colour. Research on herbal-based hair dyes has expanded with the growing interest in natural ingredients. The bark of the jamblang tree (Syzygium cumini L.), which produces a black pigment, has long been utilised in various crafts. This potential makes it a candidate for natural hair dye. This study examines the use of ethanol extract from jamblang bark in the formulation of herbal hair dye and its effectiveness in producing a black colour. The research aims to investigate the utilization of ethanol extract from jamblang bark (Syzygium cumini L.) as an herbal hair dye. The focus is on evaluating the extract's effectiveness in a formulation with pyrogallol, copper (II) sulfate, and xanthan gum, as well as determining the optimal concentration to achieve black hair colour. The method for preparing the hair dye formulation involved the use of ethanol extract from jamblang bark in varying concentrations of 5%, 7.5%, 9.5%, and 11.5%, with the addition of 2% each of pyrogallol, copper (II) sulfate, and xanthan gum. Distilled water was used as the solvent. The dyeing process was conducted by immersing 200 strands of grey hair in preparation for 4 hours, followed by visual observation of colour changes. Colour stability was tested through 15 wash cycles and exposure to sunlight for 5 hours. An irritation test was also conducted on volunteers to evaluate the safety of the hair dye preparation. The study's results indicate that increasing the concentration of ethanol extract from jamblang bark affects the effectiveness of hair dyeing. The optimal formulation was achieved at a 7.5% extract concentration with the addition of 2% pyrogallol, 2% copper (II) sulfate, and 2% xanthan gum, which resulted in black colour. Stability tests showed that the colour remained unchanged after 15 wash cycles and 5 hours of sunlight exposure. Furthermore, the irritation test on volunteers demonstrated that the preparation did not cause skin irritation reactions. Thus, the ethanol extract of jamblang bark has the potential to serve as a safe natural hair dye, offering good colour stability and effectiveness in darkening grey hair.